Spatio-temporal variability of processes across Antarctic ice-bed–ocean interfaces - Florence Colleoni (Nature Portfolio, 2018)
Understudied in the Antarctic system are the subsurface interfaces between ice-sheet, ocean and geological substrate. Here, the authors review our understanding of these components and propose new avenues of holistic dynamic modeling to achieve a unified understanding of past, present and future polar climate.